Rola trenera pracy w zakładzie aktywności zawodowej – propozycje działań w ramach prowadzonej rehabilitacji zawodowej osób z niepełnosprawnościami na podstawie modelu zatrudnienia wspomaganego - Ochońska, Magdalena (Kultura-Społeczeństwo-Edukacja, 2023)
Because of labour market changes and the new forms of labour provisions required necessary adaptation, in the near future there might be a need of creating innovative and elastic forms of support for persons with disabilities from institutions that supporting this group. At the same time we could see the changes in perception of the laws of persons with disabilities for full participation in social or labour life defined according with The Convention On the Rights Of Persons With Disabilities. There are slow changes in the system of support persons with disabilities, also in the access to various forms of rehabilitations. Still, between institutions that support this group in Poland main role plays vocational activity facilities, one of their goal is to provide vocational and social rehabilitation. According with Strategia na rzecz Osób z Niepełnosprawnościami na lata 2021–2030, the share of supported employment should increase. Up to now this was realised as a third sector actions, but now it will be the action model implemented to the national system. The goal of this article is an elaborating of the propositions about an including the elements of supported employment into everyday work in vocational activity facilities. It could help to increase the effectiveness of rehabilitation provided in those facilities. This article has the research and practical character. Based on the mixed research: quantitative (questionnaire), qualitative (data analysis) and author experience presents an example of labour model in vocational activity facility with elements of supported employment. This model is only a theoretical construct that will be implemented and evaluated in next articles.